Best practice of ordinary national educational testing use in basic education level: a multiple-case study - Prommaboon, Treekom; Boongthong, Siriluck; Tochot, Prasong; Imboonta, Boontawee; Intakanok, Prachit; Prachagool, Veena; Nuangchalerm, Prasart (Journal of Education and Learning (EduLearn), 2024)
This research employed a mixed-methods approach to explore the best practices of ordinary national educational testing (O-NET) to improve the quality of basic education. The methodology was divided into four phases, the first of which was a survey and analysis of the current situation at O-NET. The sample group was made up of representatives of the school under the office of the basic education commission (OBEC), primary education, comprising the school administrators and teachers teaching in four subjects. Phase 2, “multiple case study,” is qualitative research by selecting specific case studies for 10 primary schools based on criteria for selection and collecting data through in-depth interviews. A semi-structured interview form was completed by 30 key informants. Phase 3, the synthesis (draft) of best practices, and phase 4, the checking and proposing of best practices by 25 assessors. The results showed the best practices in using the test results of O-NET to improve the quality of basic education were 4 components: i) school management (16 practice guidelines); ii) learning management (10 practice guidelines); iii) student promotion (6 practice guidelines); and iv) parent communications (3 practice guidelines). The best practices were in accuracy, propriety, feasibility, and utilization; all were at the highest level.